Analisis Kebergunaan: Aplikasi Pemesanan Fastboat Berbasis Mobile di Bali - Bagus Made Sabda Nirmala (Puslitbang Sekawan Institute Nusa Tenggara, 2020)
The technology usefulness are very important especially on the transportation industry. Watertransportation still important in Bali. This kind of transportation very useful to help tourist orlocals reach the remote island like Nusa Penida or Nusa Lembongan. In Bali also known asfastboat. This one very popular to use to visit Nusa Penida, one of the small islands in the eastof Bali. But the conditions today, everyone who wants to go to Nusa Penida, always take offastboat transportation, by buying fastboat tickets on Sanur Beach, Kusamba Beach orPadang Bai Harbour. Tourists who come to Bali also do the same thing if they want to go toNusa Penida. tourists still have to use social media to search for fastboat tickets and book viachat application. In addition, there are also those who are looking for boat tickets bycontacting one by one the existing boat operators either by telephone, or whatsapp shortmessage. This condition is a problem because tourists and people who want to go there mustspend time longer. In addition, there is still potential for crime through social media, forexample selling fake fastboat tickets by unofficial agents. because not all boat ticket sellersare partner with existing official fastboat operators. This study aims to examine the usefulnessor usability of android mobile applications for online booking of fastboat tickets from Bali toNusa Penida or return. In addition, this research has succeeded in building applications thatcan facilitate users to compare boat ticket prices and can order at once on the same platform.This usability test contains 5 aspects of usability: learnability, efficiency of use, memorability,error and satisfaction. The usability test results in this application showed 83.3% stated theease of use of the application login that contained aspects of efficiency of use, memorabilityand satisfaction.